The Relationship between Total Carbondioxide and Lactate Levels to Hypovolemic Shock Post-CABG in ICU Dr Kariadi General Hospital - Hayanto, Aria Pratama; Widyantoro, Adhitya Putra; Jatmiko, Heru Dwi; Sasongko, Himawan (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2026)
Background: A total of 2.4% of patients after Coronary artery bypass grafting (CABG) required reoperation due to postoperative bleeding leading to vasodilatory shock syndrome. The condition of metabolic acidosis was common in shock patients where a low serum TCO2 value could be used as an indicator. Lactic acidosis was the most common cause of metabolic acidosis in hospitalized patients. TCO2 measurement was more useful to determine anion gap, but still rarely utilized. The correlation of TCO2 and lactate levels were not known well in hypovolemic shock. This research aims to analyzing the correlation of serum TCO2 values and lactate levels to the condition of hypovolemic shock post CABG.Method: This study was an observational prospective cohort study. 23 subjects were post-CABG patients undergoing treatment at Dr. Kariadi as of January-February 2023. Data were obtained from hemodynamics status, measuring serum TCO2 and lactate levels in blood samples from patients taken 1 hour after surgery. The data were then processed using fischer’s exact test.Results: 26.1% subjects were experiencing hypovolemic shock post-CABG. Correlation analysis between lactate, TCO2 artery, and TCO2 vein to the condition hypovolemic shock post-CABG showed strong correlation (p=0.009; p=0.003; p=0.003). The correlation of lactate levels and TCO2 values both artery and vein resulted strong correlation (p=0.026). Cut-off lactate level delta was 5.8; cut-off TCO2 Artery delta was 20.5; cut-off TCO2 vein delta was 21.55 which were all measured using the ROC curve.Conclusion: TCO2 serum and lactate levels have strong correlation to the condition hypovolemic shock post-CABG patients.